PENGELOMPOKAN KASUS TUBERKULOSIS PARU DAN UPAYA PROMOSI KESEHATAN DI WILAYAH MLATI II SLEMAN YOGYAKARTA - hendra rohman; Nabila Rizki Putri Utami (STIKes Al-Insyirah Pekanbaru, 2019)
The case of pulmonary tuberculosis in the Mlati II Health Center Sleman Regency has increased. Data presentation was only limited in tables and graphs. Mapping of patient health data in an area needs to be done to facilitate the health promotion strategy. The aim was to identify the distribution of cases of pulmonary tuberculosis through mapping for health promotion efforts. Quantitative descriptive research. The population was pulmonary tuberculosis patients in 2015-2017. A sample of 43 people. The instrument uses Quantum GIS version 1.8 and kernel density analysis was carried out. Results: The highest cases of pulmonary tuberculosis were in the Sumberadi sub-district of 17 people, men were more susceptible, especially productive age. The highest area of ​​cases is in Ngentak Hamlet. Grouping cases in the western region of Sumberadi Subdistrict and in the south of Tirtoadi Subdistrict, and spread in the central, northern and eastern regions of Mlati District. Health promotion was carried out at the neighborhood and community unit. Conclusion: There were groupings of cases of pulmonary tuberculosis in the Sumberadi and Tirtoadi regions. Need counseling about air ventilation. The use of medical record data for mapping was expected to be the basis for consideration in carrying out health promotion plans.